GAME-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING INNOVATION IN SURAH AD DUHA: A LITERATURE REVIEW - Sustriana Sustriana; Muhamad Slamet Yahya (LP2M IAI Al-Khairat Pamekasan, 2026)
This study examines an innovative approach in teaching Islamic Religious Education (PAI) subjects by using learning techniques that involve games to learn Surah Ad Duha. The research is carried out by reviewing and analyzing various existing literature to find out the extent to which the learning method through games can help students better understand the meaning and teachings in Surah Ad Duha. The results of the study show that teaching and learning strategies that use games are proven to increase students' enthusiasm for learning, deepen their understanding, and help students better appreciate the values of Islamic teachings. This research makes an important contribution in developing a more efficient way of teaching PAI and attracting students' interest.